2003
DOI: 10.1128/iai.71.9.4901-4907.2003
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Prime- Mycobacterium bovis BCG Boost Vaccination Strategy for Cattle Induces Protection against Bovine Tuberculosis

Abstract: The variable efficacy of bacillus Calmette-Guérin (Mycobacterium bovis BCG) in protecting humans and cattle against tuberculosis has prompted a search for a more effective vaccination regimen. A prime-boost strategy was investigated in cattle naturally sensitized to environmental mycobacteria by using a combination of three DNA vaccines coding for Hsp 65, Hsp 70, and Apa for priming, followed by a boost with BCG prior to experimental challenge with virulent M. bovis. Controls were vaccinated with DNA or BCG al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 32 publications
5
57
0
4
Order By: Relevance
“…bovis, or a protein vaccine as a boost [28][29][30]. None of these vaccines were significantly more potent than BCG and some were less potent, including a DNA 13 vaccine that was found to be equivalent to BCG in an inbred mouse model but clearly inferior to BCG in the more stringent guinea pig model [26,27].…”
Section: Rbcg30 and Rbcg30mb-immunized Animals Exhibit Greater Protecmentioning
confidence: 99%
See 1 more Smart Citation
“…bovis, or a protein vaccine as a boost [28][29][30]. None of these vaccines were significantly more potent than BCG and some were less potent, including a DNA 13 vaccine that was found to be equivalent to BCG in an inbred mouse model but clearly inferior to BCG in the more stringent guinea pig model [26,27].…”
Section: Rbcg30 and Rbcg30mb-immunized Animals Exhibit Greater Protecmentioning
confidence: 99%
“…None of these vaccines were significantly more potent than BCG and some were less potent, including a DNA 13 vaccine that was found to be equivalent to BCG in an inbred mouse model but clearly inferior to BCG in the more stringent guinea pig model [26,27]. The most impressive vaccine regimens reported have utilized a DNA prime or a prime comprising M. bovis culture filtrate in a CpG oligodeoxynucleotide-containing adjuvant and a BCG boost; these prime-boost vaccine regimens showed a trend toward improvement over BCG in several parameters studied in cattle [29,31].…”
Section: Rbcg30 and Rbcg30mb-immunized Animals Exhibit Greater Protecmentioning
confidence: 99%
“…DNA vaccines have induced minimal protection against TB when used alone, although some protection has been observed when mycobacterial DNA was combined with DNA encoding co-stimulatory molecules CD80 and CD86 [67] or combined with an adjuvant [68]. More encouraging results have been reported when DNA vaccines have been used in heterologous prime-boost regimes with BCG, and priming or boosting with mycobacterial DNA vaccines induced greater protection than with BCG vaccine alone [44,69,70]. Similarly, TB protein vaccines have induced little protection in cattle when used alone, whereas when coadministered at adjacent sites with BCG have induced protection that was better than that observed with BCG alone [45,71].…”
Section: New Tb Vaccines Evaluated In Cattlementioning
confidence: 66%
“…Antigen-specific post-vaccination T cell central memory (Tcm) immune responses can be measured 12 weeks post-vaccination using a Cultured ELIS POT technique and serve as a positive predictor of vaccine efficacy [46••, 47, 77]. IL-17 responses to mycobacterial antigen have also been used as a positive predictor of vaccine efficacy post-vaccination, while post-challenge, IL-17 expression correlated with disease severity [44,56]. A population of poly-functional T cells that simultaneously release IFN-γ, IL-2, and TNF-α have recently been investigated from cattle naturally infected with M. bovis and revealed that these CD4 + T cells express a CD44 hi CD45RO + CD62L lo T-effector memory (TEM) phenotype which is associated with pathology [78].…”
Section: Correlates Of Vaccine Efficacy or Diseasementioning
confidence: 99%
“…The release of IFN-g in infected cattle may be caused by the bacterial burden during later stages of infection, after the immune control of the pathogen has failed, leading to the destructive effects of Th1 response on tissues. Notwithstanding the negative effects that IFN-g release may cause, the specific production of IFN-g is a parameter widely used in vaccine studies (Skinner et al 2003, Waters et al 2009, De Souza et al 2012 because in mice, IFN-g production seems to be substantial for protection. Mice in which the IFN-g gene was disrupted were unable to contain or control a normally sublethal dose of M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%